(untitled) (Journal of responsible AI & ethics, 2026)
The field of Artificial Intelligence (AI) has evolved significantly over the past several decades, from its conceptualization in early computing to its pervasive application in modern-day systems. As AI systems become increasingly integrated into various sectors, ethical considerations have become a central concern. This paper examines the historical development of AI ethics, tracing its roots from early philosophical questions about machine intelligence to contemporary debates on bias, transparency, and accountability in AI systems. The study highlights the pivotal ethical frameworks that have emerged over time and their influence on the design and deployment of AI technologies. The research draws upon both historical data and modern perspectives to understand how AI ethics has been shaped by technological advancements, societal concerns, and regulatory efforts. It also explores the future trajectory of AI ethics, particularly with regard to emerging issues such as autonomous systems, privacy concerns, and global AI governance. The paper concludes with a discussion of future prospects for AI ethics, emphasizing the importance of cross-disciplinary collaboration, regulatory frameworks, and ethical guidelines to ensure that AI serves the global good while minimizing harm.